Development of fourth grade math teaching materials using the PBL model on student learning outcomes - Ahmad Landong; Dini Ayuningsih; Inge Dita (Institute of Computer Science (IOCS), 2023)
This study intends to elaborate on a material as a mathematics learning material with a Problem Based Learning system for 4th grade elementary school children in one of the elementary schools in the city of Medan in order to convey teaching material that will be delivered in learning. Exploration here is a formative test in the form of improvement which will be adjusted to the Four-D form. Judging from the consequences of the assessment of several experts, in particular: material experts, linguists, as well as media experts, it can be seen that factual learning material with a problem-based system meets the standard will be valid normally 0.76. While the results of the examination of the evaluation of the fairness of student educator sheets obtained, the problem-system statistical material met functional standards with a typical score of 95%.